UNIVERSITY EXTENSION AS A STRATEGY FOR PROMOTING THE MATERIALS ENGINEERING COURSE: RESULTS AND IMPACTS OF PROJEMAT - Figueiredo, Luis Felipe Siqueira; Padua, Gabriel Fabricio Rocha de Carvalho; Silva, Samuel Corrêa da; Rosas, Nalanda Said; Rocha, Gabriela Silva da; Estebanez, Leslie Azevedo; Junior, Julio Simonetti Martins; Reinaldo, Juciklécia da Silva (Seven Editora, 2025)
University extension projects play a strategic role in promoting scientific and professional fields that are still little known to society. This study reports and analyzes the actions of the Extension Project for the Promotion of the Materials Engineering Program at the School of Technology of the State University of Amazonas (PROJEMAT), aimed at disseminating the Materials Engineering program at UEA and strengthening its integration with schools, industries, and the community. Regarding methodology, the actions were structured in differ-ent areas, including interactive lectures in high schools, technical visits to local industries, guided tours of university laboratories, student welcoming pro-grams, workshops, and continuous dissemination through social media. The results showed significant engagement of 815 high school students who par-ticipated in the lectures, with a measurable increase in interest in the program and direct enrollments of participants. The technical visits promoted interaction with the productive sector and generated professional opportunities, while ac-ademic workshops and reception activities strengthened the sense of belong-ing among undergraduate students. Therefore, it is concluded that PROJEMAT was an effective strategy to strengthen the ties between university and com-munity, improve student training, and consolidate extension as a vector of sci-entific dissemination and professional development in the Materials Engineer-ing program.DOI: https://doi.org/10.56238/sevened2025.038-015